Právna regulácia krajinotvorby na Slovensku ako prostriedok ochrany klímy - Ľudovít Máčaj (Acta Universitatis Carolinae. Iuridica, 2024)
The article focuses on the implementation of landscaping as a purposeful activity of humans with the aim of creating and cultivating the environment around them. Landscaping is not only made up of activities with an impact on the immediate surroundings of a human, but also has a deeper social meaning – it affects the environment as a whole. However, it also has a significant impact on climate protection. Actions taken with the intention of protecting and improving the landscape that immediately borders the built-up area of municipalities in which humans reside can have a wider impact indirectly, but even directly, influence the climate. Although landscaping represents a separate and distinct professional activity, in the case of the Slovak Republic it is not a separate decision-making process in the field of public administration. However, its elements are present in other decision-making processes, such as land development or spatial planning. The ever-increasing voices after its codification point to the importance of this activity and the need to give it a clear legal framework, with the definition of the public interest and the goals that should be achieved during this activity. We believe that climate protection could and clearly should be among these objectives, as the measures taken in landscape design can have a direct effect on it. The article therefore focuses on the issue of landscaping and its legal definition, and also deals with whether landscaping represents an important means of climate protection. Furthermore, the article points out the individual possibilities of landscape design measures within the decision-making processes of public administration in the Slovak Republic. In the end, he brings some considerations de lege ferenda.